Interpreter mediated social work in Galicia: an approach through the MELINCO Project - Oca González, Luzia; Pérez Freire, Silvia; Casado Neira, David; Del Pozo Triviño, Maribel (Cuadernos de Trabajo Social, 2023)
The aim of this paper was to analyse communication difficulties detected in the relationship between social intervention professionals and migrants, refugees and asylum seekers who do not speak the official languages of Galicia. The focus group discussion data obtained by the MELINCO development cooperation project was subjected to qualitative analysis. This problem has been studied since the early days of social work and there are many studies examining the difficulties and challenges that arise as a result of shortfalls during communication with individuals, families and communities. The results highlight the difficulties and even the impossibility of using social work tools, instruments and principles to perform high-quality intervention. Despite the multiple strategies used by social intervention professionals during NGDO (non-governmental development organization) mediation before the different administrations, the lack of qualified interpreters in social services leads to the violation of users’ civil and social rights.